The walking dead. Fall of the Governor part one [compact disc, unabridged] - Kirkman, Robert (Kirkman, Robert. Walking dead, 2013)
Uber-villain Philip Blake journeyed from his humble beginnings directly into the dark heart of the zombie apocalypse and became the self-proclaimed leader of a small town called Woodbury. The violent dictatorship within Woodbury all comes to a head. The third book in the New York Times bestselling series.